Accelerating charge transfer via nonconjugated polyelectrolyte interlayers toward efficient versatile photoredox catalysis - Li T.; Feng C.; Yap B.K.; Zhu X.; Xiong B.; He Z.; Wong W.-Y. (Nature Research, 2023)
One of the challenges for high-efficiency single-component-based photoredox catalysts is the low charge transfer and extraction due to the high recombination rate. Here, we demonstrate a strategy to precisely control the charge separation and transport efficiency of the catalytic host by introducing electron or hole extraction interlayers to improve the catalytic efficiency. We use simple and easily available non-conjugated polyelectrolytes (NCPs) (i.e., polyethyleneimine, PEI; poly(allylamine hydrochloride), PAH) to form interlayers, wherein such NCPs consist of the nonconjugated backbone with charge transporting functional groups. Taking CdS as examples, it is shown that although PEI and PAH are insulators and therefore do not have the ability to conduct electricity, they can form good electron or hole transport extraction layers due to the higher charge-transfer kinetics of pendant groups along the backbones, thereby greatly improving the charge transfer capability of CdS. Consequently, the resultant PEI-/PAH-functionalized nanocomposites exhibit significantly enhanced and versatile photoredox catalysis. 2021, The Author(s).